Digitally-social genre fiction: citizen authors and the changing power dynamics of writing in digital, social spaces. Issue 3 (3rd March 2020) - Johnson, Miriam J.
ABSTRACT: The growth of digitally social media has given rise to the citizen author, as an author who actively chooses to forgo the traditional publishing model and seeks instead to share their works among communities on social platforms. Taking into account the nature of the medium on which they write, they use genre fiction as a means to push the boundaries of what is expected of a 'book' or narrative structure. This article shows that, by pushing back against the structure of the author-agent-publisher model, these authors engender communities around their writing and develop relationships directly with readers. These digital villages proliferate around genre writing in online spaces, creating a shifting power dynamic between the publishing industry and the writers who choose to work in these digital spaces, blurring the differential between 'high' and 'low' art and addressing the issues of gender in genre fiction.